CDC Directed Funding Improves Foodborne Outbreak Reporting in U.S. States, 2009–2022 - Madhura S. Vachon; Alexandra R. Edmundson; Alice E. White; Thuy N. Kim; Hillary A. Booth; Melanie J. Firestone; Elaine J. Scallan Walter; Craig W. Hedberg (Journal of Food Protection)
Through Epidemiology and Laboratory Capacity (ELC) cooperative agreements, the US Centers for Disease Control and Prevention (CDC) has funded three programs focused on enhancing foodborne illness outbreak detection and response at the state level—the Foodborne Diseases Centers for Outbreak Response Enhancement (FoodCORE), the Integrated Food Safety Centers of Excellence (Food Safety CoE), and OutbreakNet Enhanced (OBNE). Data from the CDC’s Foodborne Disease Outbreak Surveillance System (FDOSS) were used to assess the effect of ELC-funded foodborne programs on single-state foodborne illness outbreak reporting from 2009 to 2022. Based on 2022 program status, participation in these programs was associated with higher rates of reporting compared to states not enrolled in any ELC programs. Average foodborne outbreak reporting rates per million population were 1.54 for states enrolled in No Programs, 2.40 for OBNE states, 3.75 for FoodCORE states, and 4.16 for Food Safety CoE states. For Salmonella, Shiga toxin-producing E. coli, and Listeria (SSL) outbreaks, average reporting rates per million population were 0.37 for states enrolled in No Programs, 0.46 for OBNE states, and 0.69 for FoodCORE and 0.67 for Food Safety CoE states. Overall ELC funding was associated with increased outbreak reporting rates. A one-dollar increase in average ELC funding was associated with an estimated 0.88 (95% CI 0.69, 1.07) unit increase in the single-state foodborne outbreak reporting rate and an estimated 0.14 (95% CI 0.09, 0.19) unit increase in the SSL outbreak reporting rate. Federal support for public health surveillance improves the detection and reporting of foodborne illness.